AKTUALISASI AL-QUR’AN DI ERA MODERN - Acep Muwahid Muhammadi (Universitas Islam Depok, 2022)
As a guide to human life, of course the Qur'an does not only discuss the divine (spiritual) aspect but also includes the temporal (worldly) aspect of man; not only related to mental problems but also external problems; covers not only personal problems but also social problems, not only occult problems but also scientific problems. Science and technology are part of human needs - have many roles in the happiness of human life, they must also receive a spark from God's Word. So, in general, Muslims think that the Qur'an does not contradict scientific findings, instead it gives a signal for humans to develop it in accordance with the Qur'an's invitation to continuously meditate on Allah's verses. Like scientific interpretation, it is also an ijtihad that can be scientifically proven even though it still has shortcomings. At the same time, the psychological effect of this version of the interpretation on the reader is much stronger than other interpretations due to the scientific evidence - which is often undeniable and can be reviewed by anyone using the same method.